(untitled) - Reader's Digest Association (Chicago, 2013)
Explore Yellowstone National Park and see its natural wonders. Watch Old Faithful, enjoy the wildlife, and learn about Yellowstone's past.
Keywords: Địa chất học,Geology; Công viên đá vàng Quốc gia,Yellowstone National Park